The Media, Implementation of the Nigerian National Communication Policy, and Citizens’ Participation in Development - Suleiman, Joshua (European Scientific Journal, ESJ, 2018)
This study examined some of the objectives, functions and implementation strategies of the Nigerian National Communication policy for the print and the broadcast media. The general aim of the policy was the development of the nation. The purpose of this study was to find out whether or not the implementation strategies of the policies had been effected by government, and the extent to which the media had performed the functions that the communication policy assigned to them, to bring about development, particularly in the rural communities. This study underscored the capability of the media to facilitate the economic empowerment and improvement in the quality of life of the rural people. The study revealed that both government and media needed to do more than necessary, and work collaboratively to reduce the growing poverty in Nigeria’s rural communities. This study adopted a conceptual framework and relied on secondary and tertiary sources.